2011
DOI: 10.1614/ws-d-11-00045.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Hybrid Bermudagrass (Cynodon dactylon× C.transvaalensis) to Three HPPD-Inhibitors

Abstract: Mesotrione, topramezone, and tembotrione inhibit 4-hydroxyphenylpyruvate dioxygenase (HPPD), an enzyme integral to carotenoid biosynthesis. Research was conducted to evaluate the response of hybrid bermudagrass following mesotrione (280, 350, and 420 g ai ha−1), topramezone (18, 25, and 38 g ai ha−1), and tembotrione (92, 184, and 276 g ai ha−1) applications. Measurements of visual bleaching (VB) and chlorophyll fluorescence yield (Fv/Fm) were evaluated 3, 5, 7, 14, 21, 28, and 35 d after application (DAA). Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
26
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 24 publications
9
26
2
Order By: Relevance
“…Cox et al (2017) noted similar turfgrass injury 2 WAT with topramezone. Elmore et al (2011b) reported turfgrass injury from topramezone was greatest 2 WAT (%47%), although in our study the turfgrass injury was greater (up to 81%). Simazine and mesotrione treatments alone maintained acceptable turfgrass injury (%13%); however, when applied in combination, considerable (up to 27%) turfgrass injury occurred.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…Cox et al (2017) noted similar turfgrass injury 2 WAT with topramezone. Elmore et al (2011b) reported turfgrass injury from topramezone was greatest 2 WAT (%47%), although in our study the turfgrass injury was greater (up to 81%). Simazine and mesotrione treatments alone maintained acceptable turfgrass injury (%13%); however, when applied in combination, considerable (up to 27%) turfgrass injury occurred.…”
Section: Resultscontrasting
confidence: 69%
“…Simazine and mesotrione treatments alone maintained acceptable turfgrass injury (%13%); however, when applied in combination, considerable (up to 27%) turfgrass injury occurred. Elmore et al (2011b) noted acceptable mesotrione turfgrass injury throughout a 5-week study. Simazine alone provided acceptable turfgrass injury (#30%), consistent with previous research (Sharpe et al, 1989).…”
Section: Resultsmentioning
confidence: 93%
“…Topramezone injury may be unacceptable to turf managers; however, this response was transient, as injury was ≤ 6% 28 DAT and 0% by 50 DAT. These responses support previous findings by Elmore et al (2011), Brosnan et al (2011), and Cox et al (2017) following topramezone applications to bermudagrass. By 21 DAT in a glasshouse, topramezone applications at 18 to 38 g ha -1 injured 'Tifway' hybrid bermudagrass 35% to 40% and 'Riviera' common bermudagrass 46% to 58% (Brosnan et al 2011;Elmore et al 2011).…”
Section: Resultssupporting
confidence: 91%
“…Tembotrione was applied to hybrid Bermuda grass (C. dactylon x C. transvaalensis) plants (Elmore et al, 2011). The herbicide caused high values of bleaching measurements and great reductions in total chlorophyll, lutein, and xanthophyll cycle pigment concentrations.…”
Section: Resultsmentioning
confidence: 99%